Analysis of Noise Level and Sound Transmission Loss of Noise Barrier Material for the Construction Site - Tan, Wei Hong; Amares, S.; Faridah, W.; Heng, W. K. (International Journal of Integrated Engineering, 2021)
The construction activities are the common noisy and annoyance work that affected the most to the human lifestyle. Those students and lecturers who stayed at the noise receptor locations might be suffering from the health impairment. The objective of this study is to assess and determine the noise level present throughout the daytime period (9AM - 12PM and 14PM - 17PM) at the respective measurement points. The analysis of noise spectrum of sound source from 125 Hz to 4 kHz is also under the topic of study. The analysis was carried out by comparing with the recommended safe noise level in term of equivalent continuous sound level (LAeq) and sound pressure level (Lp). The objective of selection the best sound transmission loss (STL) of noise barrier material among the 3 material classifications: metal, fibre and polymer is also under investigation. The experiment STL of four different types of noise barrier material was carried out in the small scale of reverberation chambers equipped with the LMS Test Lab and LMS SCADAS Mobile device. The 16 tested one-third octave frequency band which is ranged from 125 Hz to 4 kHz had been used in the experiment. The results revealed that the material of newspaper was delivered to the STL ranged from 0dB to 9.7dB within the low frequency of 125 Hz to 800 Hz. For the material of aluminium foil, it has the optimum performance with at least 5.4dB and above of STL at higher frequency ranged from 1 kHz to 4 kHz. In overall, newspaper is considered as the best noise barrier material as it could reduce the noise level more throughout the selected frequency range in this study. Even though the newspaper is insufficient durable to rain and sunlight, but it is the best noise barrier material among the 3 classifications. The experiment of material that used to cover up the newspaper which is durable to different weather will be conducted in further research.